Precision Forestry: Trees Counting in Urban Areas Using Visible Imagery based on an Unmanned Aerial Vehicle. Issue 16 (2016) - Hassaan, Omair; Nasir, Ahmad Kamal; Roth, Hubert; Khan, M. Fakhir
Abstract: This research work describes an approach to count trees in an urban environment. Furthermore it addresses the problems involved in detection of trees in aerial imagery. This work can be used to solve the problem of forest degradation and deforestation. Right now forest man labor isn't efficient enough to detect or prevent this problem. A multi-rotor UAV equipped with high resolution RGB camera was used to acquire aerial images and to count number of trees in surveyed area. Various issues involved in the robust implementation of proposed algorithm are discussed. The result of successful implementation of the proposed algorithm on multiple scenarios are also presented and we show that our naive approach is able to achieve ≈ 0.72 accuracy within reasonable amount of time.